2018
DOI: 10.1111/raq.12249
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular changes associated with fish oocyte ageing

Abstract: Post-ovulatory oocyte ageing in fish is associated with limited fertilization rate, poor embryo development, larval malformation, ploidy anomalies and various other offspring abnormalities. Many studies have focused on morphological, physiological, biochemical and histological changes that occur during oocyte ageing. However, little is known about molecular changes associated with this process. This review covers the cellular and molecular characteristics of ageing oocytes with special focus on age-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…Although we did not conduct detail monitoring in subsequent ages due to such large individual variations, we found that the oocyte growth in this phase seemed to be notably slow and even suspected to be almost halted. Only after reaching the age of 7 years, oocyte maturation is somewhat accelerated and such that 'caviar-like' oocytes are found in considerable numbers of females, implying that a certain biological signaling is essentially needed to trigger oocytes to enter the final maturation stage (Nagahama and Yamashita, 2008;Samarin et al, 2019). Unlike ovarian maturation, the process of testicular maturation was achieved relatively earlier without a lag interval intercepted between the initial and final maturation stages.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not conduct detail monitoring in subsequent ages due to such large individual variations, we found that the oocyte growth in this phase seemed to be notably slow and even suspected to be almost halted. Only after reaching the age of 7 years, oocyte maturation is somewhat accelerated and such that 'caviar-like' oocytes are found in considerable numbers of females, implying that a certain biological signaling is essentially needed to trigger oocytes to enter the final maturation stage (Nagahama and Yamashita, 2008;Samarin et al, 2019). Unlike ovarian maturation, the process of testicular maturation was achieved relatively earlier without a lag interval intercepted between the initial and final maturation stages.…”
Section: Discussionmentioning
confidence: 99%
“…Free lysine (L-lysine• HCl) is utilized for growth less efficiently than protein-bound lysine (soybean meal) in practical diets by young channel catfish (Ictalurus punctatus). Aquaculture, 159 (1)(2), 87-100. DOI: https://doi.org/10.1016/S0044-8486(97)00184-1.…”
Section: Considerações Finaismentioning
confidence: 99%
“…Oocyte ageing appears to be a complex process involving multiple pathways. Some of the cellular and molecular changes associated with this ageing process have been investigated in fish [ 4 , 5 , 6 ], as well as in other vertebrates [ 7 , 8 ]. However, the precise pathways underlying oocyte ageing have yet to be sufficiently characterized.…”
Section: Introductionmentioning
confidence: 99%